2022
DOI: 10.1155/2022/1768208
|View full text |Cite|
|
Sign up to set email alerts
|

Multislice Computed Tomography Angiography Imaging Diagnosis of Lower Extremity Arteriosclerosis in Patients with Hypertension and Its Correlation with the Level of High-Sensitivity C-Reactive Protein

Abstract: The aim of this study was to investigate the relationship between multislice computed tomography (CT) angiography (MSCTA) imaging and high-sensitivity C-reactive protein (hs-CRP) in patients with hypertension and lower extremity arteriosclerosis. 68 hypertensive patients with lower extremity arteriosclerosis were selected as the observation group, and 68 healthy volunteers were selected as the control group to compare the differences in hs-CRP. According to the degree of stenosis, the patients were further div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…2 Therefore, screening procedures are critical for the early detection of PAD and the prevention of complications, particularly limb amputation. 2,3 Globally, an estimated 200 million people suffer from occlusive arteriosclerosis, which can be life-threatening. 3 The estimated prevalence of PAD in the Asian continent is 6-10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Therefore, screening procedures are critical for the early detection of PAD and the prevention of complications, particularly limb amputation. 2,3 Globally, an estimated 200 million people suffer from occlusive arteriosclerosis, which can be life-threatening. 3 The estimated prevalence of PAD in the Asian continent is 6-10%.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Globally, an estimated 200 million people suffer from occlusive arteriosclerosis, which can be life-threatening. 3 The estimated prevalence of PAD in the Asian continent is 6-10%. 4,5 The prevalence of PAD also increases with age (20% at 40 years and 29% in those aged over 50 years).…”
Section: Introductionmentioning
confidence: 99%
“…Several cohort studies have reported that an elevated hs-CRP level is independently associated with an increased incidence of major cerebrovascular and cardiovascular outcomes (34,35). Similarly, many recent studies have shown that the hs-CRP level is positively correlated with CV risk in various clinical settings (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 98%
“…Also, hsCRP was found to be higher in Wegener’s granulomatosis cases that are in relapse, and serial CRP measurement fills the urgent need for an objective index of the activity of this disease [ 668 , 669 , 670 , 671 ]. Apart from Kawasaki disease, in which data are contrasted, some authors believe that arteriosclerosis is an autoimmune condition; hsCRP has been correlated with disease severity, and a study found that SNPs affect arterial pulse wave velocity in healthy people [ 672 , 673 ]. Studies on paroxysmal nocturnal hemoglobinuria and CRP are limited, and notably elevated CRP values can be seen in some case reports—possibly in relapses [ 674 , 675 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%